2013
DOI: 10.1051/0004-6361/201218822
|View full text |Cite
|
Sign up to set email alerts
|

The role of cold gas and environment on the stellar mass-metallicity relation of nearby galaxies

Abstract: We investigate the relationship between stellar mass, metallicity and gas content for a magnitude-and volume-limited sample of 260 nearby late-type galaxies in different environments, from isolated galaxies to Virgo cluster members. We derive oxygen abundance estimates using new integrated, drift-scan optical spectroscopy and the base metallicity calibrations of Kewley & Ellison (2008, ApJ, 681, 1183. Combining these measurements with ultraviolet to near-infrared photometry and Hi 21 cm line observations, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
202
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(242 citation statements)
references
References 134 publications
(165 reference statements)
33
202
5
2
Order By: Relevance
“…The MZRs of the two subsets are well separated in the lower-mass part, with a mean metallicity offset of 0.5 dex, which is similar to the result found at M * > 10 8.5 M by Ellison et al (2008) in the local Universe. On the contrary, they become very close at higher masses, suggesting that the MZR is independent from the sSFR, which is more in agreement with the results of Hughes et al (2013) and .…”
Section: The Dependence Of the Metallicity On The Stellar Mass And Sfrsupporting
confidence: 89%
“…The MZRs of the two subsets are well separated in the lower-mass part, with a mean metallicity offset of 0.5 dex, which is similar to the result found at M * > 10 8.5 M by Ellison et al (2008) in the local Universe. On the contrary, they become very close at higher masses, suggesting that the MZR is independent from the sSFR, which is more in agreement with the results of Hughes et al (2013) and .…”
Section: The Dependence Of the Metallicity On The Stellar Mass And Sfrsupporting
confidence: 89%
“…A similar anti-correlation between HI mass excess and metallicity has been found by Robertson et al (2013). Hughes et al (2013) also find the anti-correlation between metallicity and gas mass at fixed stellar mass in a volume-limited sample of 260 nearby late-type galaxies. Interestingly, the relationship is nearly invariant to the environment when going from clusters to the field.…”
Section: The Stellar Mass-metallicity-sfr Relationshipsupporting
confidence: 83%
“…Bothwell et al 2013;Hughes et al 2013). De Rossi et al (2015b) obtained that dependence in the case of GIMIC galaxies while Lagos et al (2016) found similar results by performing a principal component analysis over different galaxy properties in the EAGLE Ref-L100N1504 simulation.…”
Section: F U N Da M E N Ta L M E Ta L L I C I T Y R E L At I O N a N mentioning
confidence: 66%
“…Finally, other authors claimed that there is no significant dependence of the observed MZR on the SFR (e.g. Hughes et al 2013;Sánchez et al 2013Sánchez et al , 2017.…”
Section: Introductionmentioning
confidence: 95%